Enantioseparation and a comprehensive spectroscopic analysis of novel synthetic cathinones laterally substituted with a trifluoromethyl group - Dobšíková, K; Javorská, Ž; Paškan, M; Spálovská, D; Trembulaková, P; Herciková, J; Kuchař, M; Kozmík, V; Kohout, M; Setnička, V (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2023)
Recently, the number of structural modifications of synthetic cathinones has been growing making them the second largest group of new psychoactive substances in Europe. Although they are abused because of their various psychoactive effects, some compounds from this group also serve as pharmaceuticals. Since synthetic cathinones are chiral molecules with one chiral center, their biological, toxicological, and pharmacological properties may significantly differ according to their absolute configuration and enantiomeric excess. In this study, we have synthesized two substances bearing a pharmacologically interesting trifluoromethyl group and developed a chiral liquid chromatography method using a polysaccharide chiral stationary phase to separate the corresponding enantiomers of both these drugs. Subsequently, we utilized molecular spectroscopic methods including chiroptical (electronic circular dichroism and vibrational circular dichroism) and non-polarizable (infrared and ultraviolet absorption) spectroscopies. In combination with density functional theory calculations, we have obtained stable conformers of selected enantiomers in solution and their relative abundances, which we used to simulate their spectra. The experimental and calculated data have been used to elucidate the 3D structure of the enantiomerically pure compounds and assign the absolute configuration of all prepared compounds.
Keywords: Methcathinone; Chiral separation; Chiroptical spectroscopy; Synthetic cathinones; DFT calculations